(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
At the outset, we note that computer technology (CT), the use of information and communication technology (ICT), computer-assisted learning (CT), multimedia technology learning (MT) and similar concepts have been taken for granted in education in recent decades. Increasingly, they are used by teachers, as well as students directly in teaching or individual (independent) student learning